Peran Guru Pendidikan Agama Islam Dalam Meningkatkan Motivasi Belajar Peserta Didik Di SMP Negeri 1 Ujan Mas - Fuspita; Nur Jannah (GHAITSA : Islamic Education Journal, 2025)
The purpose of this study is to determine the role of Islamic Religious Education teachers in fostering students' morals, to determine the strategies of Islamic Religious Education teachers in fostering students' morals and to determine the factors that inhibit the development of students' morals. Based on the methods and types of facts used, this search is protected in qualitative research so that it will produce descriptive information in word structure. This research is a qualitative field research, the form of research is qualitative descriptive using data collection techniques, namely observation, interviews, and documentation. Furthermore, data analysis was carried out using qualitative descriptive analysis. The results of the study showed that: the morals of students at SMP Negeri 1 Ujan Mas were good, friendly, and polite. However, there are still some whose morals need to be improved such as respecting, obeying, being polite, being polite, and shaking hands when meeting. The goal is for students to have an attitude of tolerance towards fellow human beings. The implementation of students' morals towards teachers is very important, namely respecting teachers, obeying teachers and implementing 5S and having character towards fellow friends such as helping each other, caring and loving, respecting friends' opinions, and greeting each other at SMP Negeri 1 Ujan Mas, focused on four roles, namely: As educators, mentors, motivators and evaluators in the formation of morals by holding religious activities, namely congregational Dhuhur prayers, reading the Qur'an, Istiqosah, and commemorating Islamic holidays, and the methods used in the formation of students' morals are story methods, role models, habits and demonstrations.